Alterations of high endothelial venules in primary and metastatic tumors are correlated with lymph node metastasis of oral and pharyngeal carcinoma - Shen, Hui (Landes Bioscience, 2014)
High endothelial venules (HEVs) are special blood vessels in the paracortical region of lymph nodes (LNs) and govern lymphocyte recruitment. LN metastasis has similarity to circulating lymphocytes homing to LNs, but the role of HEVs in the progression of oral and pharyngeal squamous cell carcinoma (OPSCC) is unclear. In this study, we found that HEVs experienced a series of morphological and functional changes during OPSCC progression and were correlated with LN metastasis. In 9 cases of 73 metastatic LNs, tumor emboli were located adjacent to HEVs or just out of the vessels but not lymphatic channels. Gap junctions of tumor cells close to HEVs decreased or disappeared, and gaps were left at contact points where tumor cells attached to the HEVs. Moreover, the proliferation rate of endothelial cells of HEVs was the highest in metastatic LNs. Finally, L-selectin was detected in both primary and metastatic tumors, and it facilitated tumor cells adhering to LNs. In conclusion, our findings suggest that remodeled HEVs are correlated with LN metastasis of OPSCC and play important role in this process by preparing premetastatic soil for cancer cell metastasis.